The enigma of weight: Figures, flux, and fitting in - Wong, Katherine; Myre, Maxine; Moules, Nancy J.; Lefebvre, Danielle; Morhun, Janelle M.; Saunders, Jessica F.; Estefan, Andrew; Russell-Mayhew, Shelly (Frontiers in Psychology, 2022)
Purpose In Western society, the measurement of weight is prioritized over a person’s bodily experience. Hermeneutic philosopher Gadamer warned against the emphasis on measurement, rather than experience, in the medical sciences. An examination of the complexity of the experience of weight provides the opportunity to shift focus from quantifying the connection between health and weight to the experience of the person being weighed. Methods This qualitative hermeneutic study aims to understand people’s experiences of weight from the interviews of professionals (n = 7) and lay experts (n = 10). Interviews were analyzed using an interpretive hermeneutic method. Results The interviews revealed that weight was experienced as a number imbued with meaning and bias, as a number that could be manipulated, and as a constant and anticipated bodily change. Weight change was expected and often unwelcomed, despite weight being a quality of the body that is always in flux. External measures of weight meant to monitor wellness and health inadvertently became an unhealthy fixation that prevented some participants from fully participating in life events and appreciating the stages their bodies were in. Conclusion Weight change is a necessary condition of being human, and bodies are and will be constantly changing. To achieve health and harmony, one must fit together the acceptance of change and their bodily experience of weight. It is often the preoccupation with weight, not weight itself, that gets in the way of living.